Jerusalem [videorecording (DVD)] - Carruthers, Bob; Viner, John; Chapman, Rupert L.; Goodman, Martin, 1953-; Lawton, Clive (Lost treasures of the ancient world., 2006)
Visit the sacred city exploring its famous walls and gates, and the mysterious temple under which so many secrets may be buried.